2022
DOI: 10.9778/cmajo.20210147
|View full text |Cite
|
Sign up to set email alerts
|

Association between chronic conditions and urinary incontinence in females: a cross-sectional study using national survey data

Abstract: Background: Urinary incontinence affects up to half of women, yet few speak to their health care provider about or receive treatment for the condition. To aid with identifying subpopulations at risk for urinary incontinence, we examined the associations between 10 chronic health conditions and urinary incontinence among Canadian adult females. Methods: We conducted a cross-sectional analysis of survey data from the Canadian Community Health Survey (2013–2014) involving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 57 publications
(67 reference statements)
1
13
3
Order By: Relevance
“…From 15 core variables, 77.9% of participants had ≥2 conditions. This rate is considerably higher than the 20.2%-50.5% multimorbidity rates reported elsewhere, 6,7,14 and likely reflects the older aged cohort with complex needs participating here. It also empirically demonstrates the increased longevity and improved survival from acute conditions which has resulted in more older adults living with multiple longterm health conditions.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…From 15 core variables, 77.9% of participants had ≥2 conditions. This rate is considerably higher than the 20.2%-50.5% multimorbidity rates reported elsewhere, 6,7,14 and likely reflects the older aged cohort with complex needs participating here. It also empirically demonstrates the increased longevity and improved survival from acute conditions which has resulted in more older adults living with multiple longterm health conditions.…”
Section: Discussioncontrasting
confidence: 65%
“…Based on the bladder incontinence question, UI was then dichotomised into continent (complete control; response "0") and incontinent (any episodes; responses "2," "3," "4," "5") groups, as has been employed elsewhere. 6,7,14,20 Previous research supports the validity and high accuracy of self-reported UI. 21 Motivated by Ho et al 12 multimorbidity was defined to capture (where possible) their core set of 20 chronic conditions.…”
Section: Instrument and Primary Measuresmentioning
confidence: 79%
See 2 more Smart Citations
“…The association between smoking and incontinence has been studied, with possible causes including the development of chronic obstructive pulmonary disease (COPD) leading to cough-related incontinence and increased peak pressure caused by coughing in chronic smokers ( Fuganti et al, 2011 ). Arthritis may be an associated factor in women because of overactive bladder that comes with age or mobility disability ( Scime et al, 2022 ; Tsai & Liu, 2009 ; Turner-Stokes & Frank, 1992 ). Cognition and physical disabilities have also been shown to be associated with incontinence as they decline, possibly due to an inability to reach the bathroom in a timely manner in those with physical disabilities ( Schumpf et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%